Development of a path tracking system for GPS denied environment - Kim, Ho Yeap; Hui, Ho Yeap; Soon, Han Wai (Penerbit Universiti Kebangsaan Malaysia, 2023)
Navigation applications such as Google Maps and Waze fail to function at global positioning system (GPS) denied environments. This is typically the primary problem faced by mountain hikers who have lost their way in a dense forest or a dementia patient who has lost his/her way. Navigation applications fail to function at places without internet signal. Also, a dementia patient may not be able to recall his original destination, rendering the GPS useless.The development of a path tracking system which does not rely on GPS is therefore necessary in such a situation. The system should be capable of guiding a person to return back to his/her original starting point without the requirement of a GPS. In this paper, we present the development of a path tracking system which exploits the inertial measurement unit embedded in a mobile phone. Doing so, the use of the GPS can be evaded. The system that we have developed consists of 3 main functions, i.e. (i) path recording, (ii) path navigation, and (iii) map generation. An SQLite database is setup in this application for storing data. Java libraries such as GraphView and Canvas are implemented to perform observation on the data obtained from the sensors and also to map the route according to the data stored into the device. The validation results show that the accuracy